Kajian Konsep Arsitektur Fungsionalisme pada Bangunan Kantor Sewa - Naufal, Muhammad Amin; Anisa, Anisa (Innovative: Journal Of Social Science Research, 2025)
This study examines the application of the functionalism architectural concept in rental office buildings in Jakarta. The research employs a qualitative approach with case studies on three buildings: Midplaza Office Building, Menara Cakrawala, and The Plaza Office Tower. The study focuses on the principles of functionalism, including "form follows function," style simplification, clear geometric forms, effective spatial connectivity and boundaries, as well as the use of simple design elements.The findings reveal that the principles of functionalism are consistently applied in these three buildings. Function-oriented design enhances space efficiency, supports user activities, and creates a modern and professional visual identity. The dominant use of glass and Aluminum Composite Panel (ACP) results in a clean, minimalist, and functional appearance. Interior spaces are designed with clear boundaries between public, semi-private, and private areas, while vertical elements such as stairs and elevators ensure effective spatial connectivity. This study concludes that the functionalism approach in architecture not only meets efficiency and functional needs but also strengthens the modern aesthetic of buildings. The study provides practical guidelines for readers and the author to create workspaces that are productive, representative, and relevant to the needs of urban companies today.